Genealogi Sanad dalam Perspektif Orientalis: Studi Kritik atas Pemikiran Michael Cook - Muhammad Ghifari; Ulfah Zakiyah (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2021)
This article review Michael Cook's thoughts on the early history of the use of isnad. Michael Cook disagrees with the opinions of the hadith scholars who said that the system of isnad only exists in Islam and is not found in other religion. Michael Cook believes that Islam is not the only sole owner of the isnad system. Long before Islam came the system of isnad had been used by previous religion, it had been used by Jews in transmitting Mishnah. Moreover Michael Cook concluded that Islam had plagiarized the Jewish isnad system. The Islamic isnad system is very closely related to the Jewish isnad system which both have similarities in many thing. Therefore, Michael Cook believes that the Islamic isnad is a plagiarism of the Jewish isnad system. In this paper, the author analyzes Michael Cook's thoughts. There are at least two main problems that the author examines, namely what and how are the fundamental ideas (main points) of Michael Cook related to the initial use of isnad? And the second, how is the methodological foundation of Jews in carrying out criticism of isnad?